Students’ Response to Visual Scaffolding Activity in the EFL Classroom - Wahid, Kaharudin; Halim, Abdul; Syukri, Suhartini (AL LUGHAWIYAAT, 2023)
The main purpose of this research is to analyse the students' respond toward Visual Scaffolding activity in the EFL classroom. The data in this study is taken from twenty five EFL students’ reflection they have narrated based on their class participation about Visual Scaffolding activty. The researcher collected the results of their reflections through Microsoft Word documents that have been shared by the researcher before they wrote their reflective journal. Then, those reflective journal were analyzed by using thematic analysis (TA) adopted from Braun and Clarke (2006) through coding the data by underlining some words as a code. The results of the research revealed that the students perceive visual scaffolding positively and enthusiastically since it was able to support them to understand the presented material throughout the teaching and learning process in the class. The students also felt that visual scaffolding could  motivate them to study. On the other hand, there were a few students stated that they were not feel any positive changes after participating Visual Scaffolding activity in their class but they admit that Visual Scaffolding can help them to understand the learning material properly.